Rethinking Asian Drama - Deepak Nayyar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Gunnar Myrdal published Asian Drama in 1968, a work which made important analytical contributions to our understanding of development but was deeply pessimistic about Asia's future prospects. Since then, contrary to Myrdal's expectations, Asia's development has been remarkable, although transformations have been uneven across countries and unequal between people. This paper explains the conception and design of the UNU-WIDER study on Asian Transformations, which seeks to analyse the amazing story of economic development in Asia over the past 50 years. It begins with reflections on Gunnar Myrdal, the author, and rethinking Asian Drama, the book, in retrospect 50 years later. It goes on to outline the rationale and objective of the study. It then discusses some critical issues and lessons that emerge - diversity in development, history and context, economic growth and structural change, wellbeing of people, markets and governments, economic openness, and institutions and policies - to serve as a teaser. It concludes with some brief reflections on Asia's future prospects over the next 25 years.
Keywords: B20; B31; B41; O10; O20; O53; O57; P50; 330; Asian Drama; development; governments; Gunnar Myrdal; history; industrialization; institutions; markets; openness; transformations